Waste Analysis Using Lean Management on Inpatient Discharge Waiting Time at RSI Siti Hajar Mataram - Aulia Rahma; Wahyudi, Bayu; Veranita, Mira (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
The inpatient discharge process is a key indicator of hospital service quality and is closely related to patient satisfaction. Research on inpatient discharge waiting time has largely not categorized the waiting time based on the type of payment guarantor, such as BPJS Kesehatan (standard class or upgraded class), private insurance, and out-of-pocket payment. RSI Siti Hajar Mataram is facing an issue with patient discharge waiting times, which exceed 2 hours (the standard set by the Ministry of Health of the Republic of Indonesia). This study aims to analyze inefficiencies (waste) in the discharge process using Lean Management principles, in order to identify the root causes of delays. A qualitative analytic approach was employed, involving direct observation and in- depth interviews. The findings revealed that the average inpatient discharge time was 147.5 minutes (2 hours, 27 minutes, and 31 seconds), exceeding the established standard. Three types of waste were identified: overprocessing, waiting, and transportation, occurring consistently across all payer categories. Root cause analysis indicated contributing factors related to human resources, methods, materials, equipment, and the physical environment. Following the elimination of identified waste, a future-state process was proposed, resulting in reduced discharge times across all groups become less than 2 hours. These improvements demonstrate the potential of Lean Management in enhancing hospital discharge efficiency and compliance with national service standards ABSTRAK Proses pemulangan pasien rawat inap merupakan salah satu indikator pelayanan pasien di rumah sakit yang berkaitan erat dengan kepuasan pasien. Penelitian mengenai waktu tunggu pemulangan pasien rawat inap sebagian besar belum mengkategorikan waktu tunggu berdasarkan jenis penjamin pembiayaan pasien, seperti BPJS Kesehatan (sesuai kelas atau naik kelas), asuransi, dan umum. RSI Siti Hajar Mataram menghadapi permasalahan pada waktu tunggu proses pemulangan pasien baik untuk pasien dengan penjamin biaya BPJS Kesehatan sesuai kelas, BPJS Kesehatan naik kelas, penjamin umum, maupun asuransi. Penelitian ini bertujuan menganalisa waste menggunakan lean management sehingga dapat diketahui waste, akar masalah, serta perubahan lamanya waktu tunggu pemulangan pasien rawat inap apabila waste dihilangkan. Menggunakan metode kualitatif dengan observasi dan wawancara, penelitian ini memperlihatkan hasil: Proses pemulangan pasien rawat inap rata-rata adalah 147,5 menit. Ditemukan waste of overprocessing, waste of waiting, dan waste of transportation pada seluruh kategori penjamin pembiayaan pasien. Akar masalah ditemukan faktor manusia, metode, material, mesin, dan lingkungan. Setelah melakukan eliminasi waste ditemukan future condition menjadi kurang dari 2 jam. Hal ini menunjukkan bahwa lean management dapat membantu meningkatkan efisiensi proses pemulangan pasien sehingga memenuhi standar yang ditetapkan.